The role of Zakat in alleviating the problem of poverty / Erbil Governorate as a model for the year 2022 AD - Afan Haji Salih; Abdulla Muhammad Qadr (Zanco Journal of Humanity Sciences)
Considering Zakat is the third pillar of the true Islamic religion, it has a great place in the life of Muslims and the economies of Islamic countries in general. Moreover, the statement of benefits of Zakat and its role in alleviating the problem of poverty in general and in Erbil Governorate for the year 2022 in particular, through a field study to reach this purpose, the results of this research show that the great and practical importance in solving the problems of the poor,  the needy and addressing their issues and their economic and social suffering in general and the pain of poverty in particular, as well as these results, showed great importance in solving problems of poverty among the poor and needy social groups inside the population of Erbil Governorate for the year 2022, which is what this research shows and proves it .